Eficiência do gasto da educaç\~ao fundamental municipal - Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Fundamental education is mainly provided by municipalities according to a decentralized model in which local management transforms resources transferred by the federal government into educational results that are centrally monitored. This mode of operation is conducive to the evaluation of management efficiency, since it favors the existence of a variety of management models with performance measured in a homogeneous way. We used the data from Prova Brasil from the years 2007, 2009, 2011 and 2013 to estimate measures of economic efficiency of municipal basic education, which considers as input the expenditure per student, and measures of student and school performance in order to eliminate the effect of student families. We obtained descriptive results of the behavior of schools and municipalities, and measures of economic efficiency that proved to be robust for different selections of municipalities, and persistent intertemporally. These measures show substantial differences between municipalities and states.
Keywords: I28; I23; C23; C29; 330; fundamental education; economic efficiency; Stochastic Production Frontier